Ubuntu in the worship service as heterotopia : a liturgical-ecclesiological exploration - Scott, Hilton R.; Wepener, Cas (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2020)
Through taking an interdisciplinary approach to studying liturgy, a connection has been made in this article between three theological concepts: koinonia, liturgical inculturation and the utopian ideal of inclusivity in the form of ‘heterotopias’. These concepts are all, to some degree, comparable to the African concept of ubuntu, an ideal or utopia in itself. This article aims to draw comparisons between the collection of normative ideals above and a current multicultural church context empirically researched in postcolonial and pluralistic church societies – in postapartheid South Africa. These comparisons are made as a process of critical interference by doing an empirical probe by asking ‘what is happening’, and a normative probe, which asks ‘what should be happening’. This involves investigating the actual liturgical praxis of worshipping communities in order to navigate toward and better understanding of an inclusive society as depicted by the concepts of the Rainbow Nation or Ubuntu. The conclusion shows that which ‘ought to be happening’ in worship that serves our current South African realities is – to an extent – already happening in some worshipping communities. Insights gained from the liturgical praxis of these communities can serve as best practices for other communities.